SELF-DISCOVERY IN NICOLA YOON’S EVERYTHING, EVERYTHING - Linus Rumapea; Yolanda Sibuea (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This is about self-discovery in Nicola Yoon’s Everything, Everything. The novel represents people especially teenagers who want to find themselves with a change in life, where they can do things they really want to do with reasonable restrictions from parents. This is library research and applies mimetic theory proposed by Abrams saying that literature is an imitation of the real world. The analysis is focused on self-discovery through inner self-demands and self-discovery through social supports. People who find themselves through inner demands are represented by Maddy and her mother. Maddy finds herself through her inner desire for change in her life. She wants to experience the outside world that she has never experienced. Her mother finds herself going through inner self-demands as she realizes that what she did to her daughter was wrong to have lied to her daughter that she was not ready to lose her daughter but in the end, she can accept the fact that her daughter deserves to live a life like a normal teenager. People who find themselves through social support are represented by Maddy and Olly. She gets great support from Olly. After Olly came into her life, she desperately wants to fulfill her wish to be able to experience the outside world. Olly finds himself through social support from Maddy. He is a broken home boy who wants to run away to get support from her to dare to persuade his mother to leave his abusive father. In conclusion, the author, Nicola Yoon in her novel Everything, Everything vividly portrays self-discovery.